Peta Preferensi Konsumen Purwokerto pada Komoditas Tahan Lama Impor Asal Cina - Neni Widayaningsih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2010)
Focus to domestic demand, this research detected the preference of Purwokerto communities between imported commodities from China and Non-China’s commodities. Generally, the communities relatively able to differ the commodities differences, particularly on telecommunication product. For each commodities, communities gave higher preference to Chine’s communication and audio/video product than others. The other way, they gave higher preference to several non-China’s product as garment, footwear, automotive and vehicles, computers products and other household electronics tools type. On income perspective, some Chine’s commodities was classified to normal and inferior commodities. The normal commodities identified were electronics tools for audio/video, telecommunication, computer, other kinds of electronics tools, and foot wear product. The other way, to kitchen electronic tools, automotive and vehicles, garment and toys product were classified to inferior product. To last of the fourth products, if the community income increased, they would shift their demand to non-Chine’s product. Keyworlds: China’s and non-Chine’s product, preference, normal, inferior